P120 Usefulness of the faecal calprotectin for the diagnosis of inflammatory bowel disease in patients with spondylorarthritis and no digestive symptoms. (25th January 2019) - González-Lama, Y; Matallana, V; Calvo, M; Espinosa, M; Ramos, C; Merino, C; Ruiz-Antorán, B; González-Partida, I; Vera, M I; Sanz, J
Abstract: Background: Faecal calprotectin (FC) is a biomarker of bowel inflammation widely spread in diagnosis and follow-up of inflammatory bowel disease (IBD). It is classically estimated that 5% of patients with axial spondyloarthritis (SpA) also have IBD; coexistence of both conditions has definite impact in clinical decisions. Proactive detection of both diseases should be advisable, though appropriate screening tools are still lacking. Our aim was to evaluate the usefulness of FC for the diagnosis of IBD in patients diagnosed with SpA without suggestive manifestations or previous diagnosis of IBD. Methods: Patients from a Rheumatology clinic diagnosed with SpA who met ASAS criteria and did not present digestive symptoms suggestive of IBD were consecutively included. Demographics, clinical and analytical data of SpA (uveitis, HLA B27, acute phase reactants) at the time of inclusion, and treatment history were collected. Patients with a positive FC (> 50 mg/kg) underwent ileocolonoscopy with biopsies of colon and terminal ileum. Patients who were recommended to avoid NSAIDs 2-4 weeks before stool collection and endoscopy. Results: In total, 98 patients included; 47% male, mean age 46.1 (20–74) years. BASDAI 3.6 + 2.5. HLA B27 positive in 78% of patients, high ESR in 31.6%, high CRP in 9.2%. FC positive in 49 patients (50%): mean 147 mg/kg (range 0–3038). Forty-seven underwent ileocolonoscopy: in 13 cases (26.5%), endoscopic findings were suggestive of IBD although confirmed in 8 cases (16.3%) (7 Crohn's disease and 1 ulcerative colitis). Microscopic inflammation was found in 2 additional cases. In patients with high FC levels, those with high CRP and ESR were more likely to have IBD (29% vs. 16% and 29% vs. 12%, respectively). Patients with a history of uveitis (18% vs. 12%) or psoriasis (33% vs. 16%) also had a higher prevalence of IBD, although none of those differences reached statistical significance. FC was higher in smokers (72% vs. 44%; p = 0.03). There were no significant differences regarding HLA B27. No statistically significant differences were found in FC between patients with high FC who were diagnosed with IBD and those who were not. Conclusions: In our study, patients with FC >50 mg/kg had a high prevalence of IBD, which could indicate the usefulness of FC determination as screening tool for IBD in patients with SpA and no clinical feature suggestive of IBD.